Higher Acetabular Anteversion in Direct Anterior Total Hip Arthroplasty: A Retrospective Case-Control Study. Issue 3 (October 2016) - Chen, Antonia F.; Chen, Chi-Lung; Low, Sara; Lin, Wei-Ming; Chinnakkannu, Karthikeyan; Orozco, Fabio R.; Ong, Alvin C.; Post, Zachary D.
Background: Surgical approach is known as a risk factor that influences cup malposition while performing total hip arthroplasty (THA). However, no study has been conducted comparing cup positioning between the supine direct anterior (DA) and supine direct lateral (DL) THA approaches. Questions/Purposes: (1) Is there a difference in acetabular cup positioning between supine DA and supine DL THA approaches? (2) Are there differences in complications based on acetabular cup positioning between the two approaches? Methods: From 2012 to 2014, 186 patients who underwent primary THAs using DA approach were matched with 186 patients using DL approach by body mass index, age, and gender. Cup anteversion and abduction angles were measured from standing anteroposterior pelvis radiographs by two blinded observers. The Lewinnek safe zone was used as the standard for cup positioning. Cup anteversion, abduction angles, and complications were recorded and compared. Results: Cup anteversion was on average 3° higher in the DA approach compared to the DL approach. The abduction angle for the DA approach was equivalent to the DL approach both averaging 46° to 47°. There were more DA hips outside of the safe zone (10%) for anteversion than DL (3%) hips. There were no differences in complications between DA and DL approaches. Conclusion: There is a tendency to antevert the acetabular cup when performing THAs using the DA approach, and one must be mindful of this when implanting the acetabular component.